Introduction to Agricultural Engineering Technology A Problem Solving Approach - Field, Harry L. (Springer International Publishing, 2018)
Introduction to Agricultural Engineering Technology: A problem Solving Approach is an invaluable text for agriculture students at the introductory level. The fourth edition has been thoroughly updated and reorganized to meet the current units and standards of the American Society of Agricultural and Biological Engineers (ASABE). The book aims to: Familiarize students with a wide range of applications of engineering principles to agriculture Discuss a selection of independent but related topics Advance students' problem solving abilities Each chapter lists education objects, introductory material, and example problems where appropriate. In addition problems using ISO (metric) units, are now included. The authors have added a new chapter on precision agriculture. About the Authors: Harry L. Field is an Associate Professor of Agricultural Mechanics in the Department of Biosystems and Agricultural Engineering at Oklahoma State University. John Long is an Assistant Professor of Biological Engineering in the Department of Biosystems and Agricultural Engineering at Oklahoma State University.